Edible Coatings Enhance Storability and Preserve Quality of Kiwiberry (Actinidia arguta L.) cv. Ken’s Red - Adriana C. Guerreiro; Custódia Gago; Dário Passos; Jaime Martins; Sandra Cruz; Fernão Veloso; Rui Guerra; Maria D. Antunes (Horticulturae)
Kiwiberries, an emerging fruit variety with increasing consumer demand, face significant commercialization challenges due to their short shelf life. This study evaluates the effectiveness of edible alginate-based coatings in extending the shelf life of kiwiberries. Two emulsion types—coarse (Coarse) and nanoemulsions (Nano)—and two application methods—spraying (Spray) and dipping (Dip)—were tested. Additionally, the use of visible/near-infrared (Vis-NIR) spectroscopy for non-destructive quality monitoring was explored. Coatings were prepared with 2% (w/v) alginate (SAlg) enriched with eugenol (Eg) and citral (Ct) at their minimum inhibitory concentrations (MICs) of 0.10% and 0.15%, respectively, as well as at double these concentrations. This resulted in a total of ten different treatments. The fruits were stored at approximately 5 °C, with evaluations conducted after 5 days, 2 weeks, and 4 weeks. Quality parameters, including color, firmness, soluble solid content (SSC), dry matter, weight loss, decay, total phenolic content (TPC), flavonoids, DPPH, FRAP, and malondialdehyde (MDA) levels, were analyzed. Over the storage period, color and SSC increased, while firmness decreased. Weight loss and MDA levels showed the most significant changes, particularly in treatments with higher essential oil concentrations. Notably, treatments such as SAlg Spray, SAlg Dip, SAlg Ct 0.15 + Eg 0.1 Nano Spray, SAlg Ct 0.15 + Eg 0.1 Nano Dip, and SAlg Ct 0.15 + Eg 0.1 Coarse Dip demonstrated superior preservation of kiwiberry quality. Moreover, Vis-NIR spectroscopy proved valuable for distinguishing between coating treatments, highlighting its potential for non-destructive quality assessment.